The Global Burden of Multidrug-Resistant Tuberculosis: An In-Depth Review of Catastrophic Costs, Patient Burdens, and Strategies for Sustainable Healthcare Solutions - Alotaibi , Khalid Matar Zaid; Alotibi, Afet Mater Zaid; Alotaibi , Muteb Qayyed; ALOTAIBI, FARAH OJAYR SIRAJ; ALOTAIBI, MUTLAQ MATLA Fahad; ALOTAIBI, MUNIF RIDHA SHUKR; Alotaibi , Ali Mutlaq; ALOTAIBI, Ghannam Munawir Shukr; Alzuhiri, Mushary Abdullah; Arishi, Ibraheem Yahia (Journal of Ecohumanism, 2024)
Background: Multidrug-resistant tuberculosis (MDR-TB) poses a significant global health challenge, with approximately 500,000 new cases reported in 2020, predominantly among vulnerable populations in low- and middle-income countries. The World Health Organization (WHO) aims to mitigate catastrophic costs associated with TB treatment, which often exceed 20% of a household's annual income, leading families into severe financial distress. This systematic review and meta-analysis aimed to assess the global burden of catastrophic expenditures related to MDR-TB, focusing on patient and family financial impacts. Methods: A comprehensive literature search was conducted across five databases (CINAHL, MEDLINE, Embase, Scopus, and Web of Science) and grey literature sources, utilizing relevant keywords related to MDR-TB and cost implications. Studies were selected based on their relevance to catastrophic costs incurred by MDR-TB patients. Results: The analysis revealed that the financial burden for MDR-TB patients is significantly higher than for drug-susceptible TB (DS-TB) cases, with treatment costs ranging from $2,423 in Peru to $14,657 in Tomsk, Russia. Factors influencing these costs include sociodemographic characteristics, diagnostic delays, and the duration of hospitalization. Notably, 43% of TB patients experienced catastrophic expenditures, with MDR-TB patients facing an even greater risk due to longer treatment durations and higher medication costs. Conclusions: In conclusion, the findings underscore the urgent need for effective interventions to reduce the financial burden of MDR-TB on patients and families. Enhanced drug susceptibility testing and improved healthcare access are critical for managing MDR-TB and preventing further economic devastation. Addressing these issues will be vital for achieving the WHO's end-TB strategy and ensuring sustainable healthcare solutions